How Is the Neural Response to the Design of Experience Goods Related to Personalized Preference? An Implicit View - Ma, Yongbin; Jin, Jia; Yu, Wenjun; Zhang, Wuke; Xu, Zhijiang; Ma, Qingguo (Frontiers in Neuroscience, 2018)
Owing to the subjective nature of product design evaluation, and the difficulty in measuring a product’s physical design using traditional methods, neuroscientific methods are preferred to understand the neural basis of consumers’ evaluation. In this study, we used event-related potentials (ERPs) and a revised go/no-go paradigm to investigate consumers’ neural responses to product designs. Personalized product designs and neutral landscape pictures were presented to 20 student participants randomly, while they were asked to view these product designs without making any decisions. The paired t-test and repeated measures analysis of correlation showed that the P200 and late positive potential (LPP) elicited by the most-preferred product designs were significantly higher than that of least-preferred designs, and the two components of the ERPs were positively correlated with the personalized rating scores. The results indicate that P200 and LPP might be the early and late indices of consumers’ evaluation of product designs, respectively, and may help to understand the temporal course of product design evaluation. Futher, these two ERP components can be used to identify consumers’ preferences for product designs, even for hedonic products or product’s hedonic dimensions.